2022
DOI: 10.1590/0100-29452022839
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating the adverse effects of deficit irrigation in Flame seedless grapevine via Paulsen interstock

Abstract: Using interstock with a potential genetic base is considered more recent and sustainable strategy for mitigating the water deficit. This investigation was carried out on transplant of Flame seedless (Vitis vinifera) grapevine grafted onto two rootstocks namely; Freedom (Vitis champinii x 1613C) and 1103Paulsen (vitis berlandieri x Vitis rupestris) with or without 1103Paulsen as interstock to determine its performance under deficit irrigation condition (50% of field capacity). The results indicated that Paulsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Using Paulsen 1103 as the interstock while grafting Flame seedless on Freedom rootstock (FI/P/ Fr) significantly decreased the relative water content (45.357%), transpiration rate (1.503 µg H 2 O/cm 2 .s), and stomatal conductance (0.060 cm/s) of scion leaves, which were related to the lowest values of the morphological parameters (Table 2), compared to the values of the parameters measured in Flame seedless grafted onto Freedom without an interstock (FI/Fr). These results were similar to those found by Fayek, Rashedy and Ali (2022), who reported that the Paulsen interstock caused changes in physiological parameters, such as the relative water content, transpiration rate, and stomatal conductance of the leaves of the scion grapevine. This effect might be due to the obstruction of water transport to the shoots by the interstock, which led to a reduction in the stomata and reduced the entry of CO 2 and light into the leaf (Zhou et al, 2015;Zhao et al, 2016).…”
Section: Physiological Parameterssupporting
confidence: 91%
See 2 more Smart Citations
“…Using Paulsen 1103 as the interstock while grafting Flame seedless on Freedom rootstock (FI/P/ Fr) significantly decreased the relative water content (45.357%), transpiration rate (1.503 µg H 2 O/cm 2 .s), and stomatal conductance (0.060 cm/s) of scion leaves, which were related to the lowest values of the morphological parameters (Table 2), compared to the values of the parameters measured in Flame seedless grafted onto Freedom without an interstock (FI/Fr). These results were similar to those found by Fayek, Rashedy and Ali (2022), who reported that the Paulsen interstock caused changes in physiological parameters, such as the relative water content, transpiration rate, and stomatal conductance of the leaves of the scion grapevine. This effect might be due to the obstruction of water transport to the shoots by the interstock, which led to a reduction in the stomata and reduced the entry of CO 2 and light into the leaf (Zhou et al, 2015;Zhao et al, 2016).…”
Section: Physiological Parameterssupporting
confidence: 91%
“…Beckman (2004) used the interstock to avoid spring freeze injury by modifying the bloom and harvest date of peach. In grapevine, the use of Paulsen 1103 as interstock within grafts improved the tolerance of the Flame seedless scion to drought Rashedy;Ali, 2022). The efficiency of the interstock depends on its length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased enzymatic activities were also observed by Santos et al [ 39 ] in drought tolerant citrus Rangpur lime and Citrus sunki rootstocks, which were attributed by the efficiently upregulation of APX enzyme activities that assist the elastic properties of grafted ‘Citrus latifolia Tanaka’ cell wall which increased the plant shoot growth under drought stress conditions. Similarly enzymatic activities of peroxidase were also reported to be upregulated significantly in Flame Seedless cultivar when grafted on relatively drought tolerant grapevine rootstock Paulsen [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grafting Ayvalik and Domat olive cultivars onto Gemlik rootstock showed slowly cambium cells formation, which contains greater concentrations of phenolic compounds (TP) than Sari Ulak and Memecik cultivars [ 10 ]. In grapevine, lower TP content and peroxidase activity in the grafting zone were coincided with a higher grafting compatible in Flame Seedless/Paulsen1103 rootstock than Flame Seedless/Freedom rootstock graft combination [ 11 ]. Also, Paulsen1103 was considered the most strongest compatible rootstock for Vitis vinifera cultivars which was accompanied by the lowest peroxidase activity at the grafting union than Freedom, Salt Creek and 110 Richter rootstocks [ 12 ].…”
Section: Introductionmentioning
confidence: 99%